ESTIMATING SHALLOW WATER TABLE CONTRIBUTION TO SOYBEAN WATER USE IN ARGENTINA - Horacio R. Videla Mensegue; Americo J. Degioanni; Jose M. Cisneros (European Scientific Journal, ESJ, 2015)
The existence of a shallow water table can be an important water source for rainfed agricultural production. The objective of this study is to quantify the water contribution of the water table to soybean water requirements in the center of Argentina by means of a crop simulation model that relates water balance to grain production. The model was calibrated and validated considering soil water records up to 1 m deep, and the oscillation in the water table depth and grain yield during two climatically contrasted growth seasons (2004/05 - 2005/06). The adjustment obtained between observed and simulated values was: 1.8 mm for soil humidity, between 0.26 and 0.01 m for oscillation of the water table and between 49 and 920 kg ha-1 for grain yield. The results obtained with the simulation indicate that the water table contributed between 12 and 30% of the total water used by the crop in each growing season studied. It was concluded that, in rainfed agricultural conditions, a water table oscillating between 1.5 and 2 m deep makes it possible to stabilize the yield of rainfed soybean.